Association between dietary intake of live microbes and chronic obstructive pulmonary disease: a cross-sectional study of NHANES 2007–2012 - Yifeng Xu; Zhaoqi Yan; Liangji Liu (BMC Pulmonary Medicine)
Abstract Background Diet plays a crucial role in intervening in the development of chronic obstructive pulmonary disease (COPD), yet previous studies have not investigated the impact of dietary intake of live microbes on COPD. This study aims to assess the relationship between the two. Methods Participants from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2012 were selected. The exposure variable was the estimated intake of live microbes in the diet, categorized into low, medium, and high groups. The outcome variable was COPD. A multivariable logistic regression model was used to assess the relationship between estimated dietary intake of live microbes and the risk of COPD. Results In the fully adjusted multiple logistic regression model, participants with moderate and high dietary intake of live microbes showed a negative association with the prevalence of COPD compared to those with low estimated intake, with reductions of 38% (OR, 0.62; 95% CI: 0.39–0.99, P < 0.05) and 44% (OR, 0.56; 95% CI: 0.34–0.92, P < 0.05) respectively. Additionally, subgroup analysis results remained stable with no observed interactions. Conclusion Our study suggests a negative association between higher dietary live microbe intake and the risk of COPD among adults in the United States. Trial registration ClinicalTrials.gov Identifier NCT00005154 First Posted date 26/05/2000(retrospectively registered).